MODERN MEANS OF IMMUNE THERAPHY FOR SICKLY CHILDREN WITH ALLERGIC DISEASES - L.S. Namazova; V.V. Botvin'eva; N.I. Voznesenskaya (Union of pediatricians of Russia, 2007)
The article deals with the prevention of the acute respiratory infections in a group of allergic children with the help of immunomodulators of microbial origin, in particular. The authors investigated the clinical effectiveness of ribosome immunocorrector (ribomuilum) among children with allergy (atopic diseases - bronchial asthma, atopic dermatitis, dermatorespiratory syndrome). They provide detailed information on the indices of the cytokine status, humoral and cellular immunity, eicosanoids and their changes during the preventive therapy by means of ribosome immunocorrector. Based on the obtained findings, the authors proposed an algorithm to conduct immunocorrective therapy among sickly children with allergy.Key words: acute respiratory infections, prevention, immunotherapy, bronchial asthma, atopic dermatitis, interleukins, ribosome immunocorrector.